Non-destructive evaluation of localised heat damage occurring in carbon composites using thermography and thermal diffusivity measurement. (January 2019) - Addepalli, Sri; Zhao, Yifan; Roy, Rajkumar; Galhenege, Wathsala; Colle, Marine; Yu, Jingjing; Ucur, Aziz
Highlights: New approach to detect chemical damage in composites using pulsed thermography. A method of creating controlled heat damage on CFRP in local area is proposed. Thermal diffusivity maps are proposed to characterise discolouration damage. A statistical approach has been implemented to confirm damage. Abstract: Carbon fibre reinforced polymer (CFRP) composites are now a common occurrence in the aerospace sector especially with their introduction into the aero-engine. With their ever-increasing use in harsh and extreme environments, it is important to understand their behaviour and performance when exposed to such working conditions. This paper presents a novel approach to understand the thermal degradation mechanism of CFRP composites based on the measurement of thermal diffusivity through non-destructive testing (NDT) when exposed to heat in a localised area. The study explored the suitability of pulsed thermography in detecting the physical damage caused due to localised heat exposure together with its ability to identify chemical change that occurs during the initial stages of exposure. The results showed the ability of thermography in detecting discolouration damage through the use of diffusivity measurements acquired by reconstructing the thermography dataset.